Postoperative Nocardia Endophthalmitis and the Challenge of Managing with Intravitreal Amikacin - Sikander A. K. Lodhi; G. Ashok Kumar Reddy; C. Aruna Sunder (Case Reports in Ophthalmological Medicine)
Nocardia is a rare cause of delayed onset postoperative endophthalmitis after cataract surgery and it usually carries a guarded visual prognosis. Purpose. To highlight the clinical presentation, microbiological profile, and treatment outcome in a case of nocardial endophthalmitis after manual small incision cataract surgery. Methods. This case report highlights the typical features of Nocardia endophthalmitis, which presented six weeks after undergoing small incision cataract surgery. The case was managed by pars plana vitrectomy with intravitreal antibiotics. Intravitreal amikacin was used based on microbiologic work-up. Results. The endophthalmitis part was controlled but the case developed amikacin induced macular infarction which jeopardized a good visual outcome. Conclusion. Nocardia endophthalmitis manifests late after cataract surgery in an aggressive manner and carries a poor visual prognosis. An early diagnosis and the use of correct antibiotic regimen may salvage the vision. But the present case shows that one should always be wary of potential retinal toxicity with intravitreal amikacin.